Peculiar Features of Microclimate Formation in Heated Rooms - A. E. Zakharevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper presents results of microclimate simulation that have been obtained while using the developed numerical model of heat transfer in the heated rooms. The model takes into account three types of heat transfer, namely: conductive, convective and radiant. The paper contains a qualitative and quantitative analysis of the obtained data. It has been revealed that type of a heating appliance significantly influences on distribution of microclimate parameters (air temperature and mobility, surface temperature) and level of heating comfort in the room.